Influence of Heat Treatment and the Coefficient of Friction on the Volume of Metal Removed During Grinding Steel 35 (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The role of external friction and chip contraction during microcutting by abrasive grain is showed. The method for determining the relative change in the coefficient of friction during grinding is proposed. The hypothesis about the influence of physical and mechanical properties and microstructure of steel 35 on the volume removes metal through the change in the coefficient of sliding friction of the chip by face of the abrasive grain is experimentally proved.